Isolated Oropharyngeal Muscle Spasm in a Young Child post Extubation: A Case Report - Singla, Deepak; Abullais Raheeq Gowda; Krishna, Vamshi; Tandon, Shipra (Academia Anesthesiologica International, 2020)
Agitation during emergence from anaesthesia is a documented phenomenon reported in children especially during immediate postoperative period; also Voluntary breath holding1and laryngospasm. This can lead to complications like postoperative distress, excessive crying, and anxiety. Here we report a case of postoperative respiratory distress in an 8 years old child of cerebral palsy developing severe oropharyngial spasm in the immediate postoperative period. Patient had no preoperative predisposing factors or intaraoperative events that could cause bronchospasm, laryngospasm, inadequate neuromuscular reversal or voluntary holding in the immediate postoperative period. Timely recognition and management of the condition prevented catastrophic complications like severe desaturation, hypoxic injury, negative pressure pulmonary edema or cardiac arrest.